Pengembangan Media BBC (Belajar Balita Cerdas) Rentang Umur 2-3 Tahun Berbasis Video Animasi - I Kadek Agus Darma Putra; I Made Gede Sunarya; I Gede Mahendra Darmawiguna (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2013)
This research was aims : 1) designed and implemented BBC (Smart Toddler Lesson) media during 2 - 3 years old with animation video based 2) Known Toddler Responses and teacher towards BBC  with animation video based. Subjects were toddlers aged 2-3 years by 9 people. the subject of this research was development research. The data was submit : Responses Data toward (BBC) Media Development Animation video style with used questionnaire. The data was analysed descriptively. His lesson Media was produced by used Adobe Flash CS3 and also some supporting software such as Corel Draw X5 for made and edited picture. Audacity for sound cultivate, Camtasia studio 6 for video cultivate and DVD style for animation video convertion to DVD. Form The result of this research was show that toddler responses and teacher toward BBC Media was categorize positively